An analysis of the effectiveness of the internal human resource information system at Robi Axiata Limited - Rafi, Hasibur Rahman (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2024.